2020
DOI: 10.1111/puar.13277
|View full text |Cite
|
Sign up to set email alerts
|

Politics, Competence, and Performance: Evidence from the US State Budget Agencies

Abstract: The relationship between administrative competence and political responsiveness is central to public administration theories. This study examines the conditional effects of competence on performance as moderated by politics. Synthesizing the theories of neutral competence and responsive competence, we propose a model of contingent competence. We argue that the impact of competence on performance is conditional on both the preferences of political principals and the degree of political control as indicated by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 78 publications
(111 reference statements)
0
4
0
Order By: Relevance
“…The answer to this question rests on the implicit or explicit assumptions the disciplinary sources bring to bear on the relationship between policy and administration. Although early public administration scholarship subscribed to the policy‐administration dichotomy and valorized ideals like neutral competence, public administration scholarship has for a long time made a persuasive case for the inter‐relatedness of policy/politics and administration (Gaus, 1950; Long, 1949; Svara, 1998; Wei et al, 2022; Yu & Jennings Jr, 2021). A clear implication of this position is that an understanding of policy, sans administration, is erroneous and invalid.…”
Section: Structuring Of Public Policy Pedagogymentioning
confidence: 99%
“…The answer to this question rests on the implicit or explicit assumptions the disciplinary sources bring to bear on the relationship between policy and administration. Although early public administration scholarship subscribed to the policy‐administration dichotomy and valorized ideals like neutral competence, public administration scholarship has for a long time made a persuasive case for the inter‐relatedness of policy/politics and administration (Gaus, 1950; Long, 1949; Svara, 1998; Wei et al, 2022; Yu & Jennings Jr, 2021). A clear implication of this position is that an understanding of policy, sans administration, is erroneous and invalid.…”
Section: Structuring Of Public Policy Pedagogymentioning
confidence: 99%
“…In the end, public administrators with a broad political network capacity will more often interact with their political principals. Thus it will make him more easily develop a trust-based emotional relationship with the political official, which is the key in attaining managerial leadership ranks (Schillemans, 2013;Yu & Jennings, 2021).…”
Section: Socio-political Dimensionmentioning
confidence: 99%
“…In order to comprehensively investigate the critical factors behind the representation of women in top leadership positions, this study will focus on three dimensions, as shown in Figure 1. First is the socio-political dimension, which is related to a particular area's social and political factors, such as the characteristics of the political environment and intersections of social and political phenomena (Meier, 2019;Yu & Jennings, 2021). Second, the intra-organizational dimension refers to critical determinants of women's career progress at the institutional level, such as organizational culture and leadership perceptions (Chigudu, 2021;Hentschel et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Yu and Jennings (2021) shed new light on state budget agency performance. They examine the conditional effects of competence on performance as moderated by politics by synthesizing theories of neutral competence and responsive competence, to arrive at a model of contingent competence.…”
mentioning
confidence: 99%